Differences in willingness to pay for artemisinin-based combinations or monotherapy: experiences from the United Republic of Tanzania - Virginia Wiseman; Obinna Onwujekwe; Fred Matovu; Theonest K. Mutabingwa; Christopher J.M. Whitty (The World Health Organization, 2005)
OBJECTIVE: The cost of combination treatment is thought to be one of the greatest barriers to their deployment, but this has not been tested directly. Estimates of willingness to pay were compared across four drug combinations used to treat Tanzanian children with uncomplicated malaria. The reasons behind respondents' valuations and the effect of socioeconomic status on willingness to pay were explored. METHODS: One hundred and eighty mothers whose children had been recruited into a recently completed randomized effectiveness trial of amodiaquine + artesunate (AQ+AS), amodiaquine + sulfadoxine-pyrimethamine (AQ+SP), artemether-lumefantrine (coartemether) and amodiaquine monotherapy (AQ) were interviewed about their willingness to pay for these drugs two weeks after treatment. Estimates of willingness to pay were elicited with the bidding game technique. FINDINGS: A significant difference was detected in the mean amounts respondents were willing to pay, with those who received AQ+AS willing to pay the most, followed by co-artemether, AQ+SP and finally AQ. The amounts patients' mothers were willing to pay for the artemisinin-based combinations, however, fell well short of the market costs. Socioeconomic status was not found to have a statistically significant effect on mean willingness to pay scores for any treatment group. CONCLUSION: This study shows that families who live in an area in which drug resistance to monotherapy is very high are willing to pay more for more effective artemisinin-based combination therapies. These amounts, however, are nowhere near the real costs of delivering the new drugs. Only with subsidies will artemisinin-based combination therapies realistically have any impact.